Expression patterns of HENMT1 and PIWIL1 in human testis: implications for transposon expression. Issue 4 (October 2017) - Hempfling, A L; Lim, S L; Adelson, D L; Evans, J; O'Connor, A E; Qu, Z P; Kliesch, S; Weidner, W; O'Bryan, M K; Bergmann, M
Abstract : This study aimed to define the expression patterns of HENMT1 and PIWI proteins in human testis and investigate their association with transposon expression, infertility sub-type or development of testicular germ cell tumours (TGCTs). Testis biopsies showing normal spermatogenesis were used to identify normal localisation patterns of HENMT1 and PIWIL1 by immunolocalisation and RT-PCR after laser microdissection. 222 testis biopsies representing normal spermatogenesis, hypospermatogenesis, spermatogenic arrests, Sertoli cell-only (SCO) tumours and TGCTs were analysed by RT-qPCR for expression of HENMT1/PIWIL1/PIWIL2/PIWIL3/PIWIL4 and LINE-1 . Additionally, HENMT1 -overexpressing TCam2 seminoma cell lines were analysed for the same parameters by RT-qPCR. We found that HENMT1 and PIWIL1 are coexpressed in pachytene spermatocytes and spermatids. Expression of HENMT1, PIWIL1 and PIWIL2 was mainly dependent on germ cell content but low levels of expression were also detected in some SCO samples. Levels of HENMT1, PIWIL1 and PIWIL2 expression were low in TGCT. Samples with HENMT1, PIWIL2 and PIWIL4 expression showed significantly ( P < 0.05) lower transposon expression compared to samples without expression in the same histological group. HENMT1-overexpressing TCam2 cells showed lower LINE-1 expression than empty vector-transfected control lines. Our findings support that the transposon-regulating function of the piRNA pathway found in the mouse is conserved in adult human testis. HENMT1 and PIWI proteins are expressed in a germ-cell-specific manner and required for transposon control.